Ironi Dalam Memori Ruang Waktu Analisis Trauma Jiwa Sebagai Ide atau Refleksi karya Dengan Pendekatan Psikoanalisis Freud - Wahyudi, Tri (Institut Seni Indoensia Surakarta, 2012)
In psikoanalitika viewpoint, experiences during early life can and will shape his personality during later life, so that psychological problems in adulthood will be influenced by childhood trauma or difficulty. As adults most people do not remember that there's something to be started when they were still traumatized childhood and memories of the trauma will be hidden in their subconscious. Theory of psychoanalysis based on the application of the theory developed by Freud to focus on the structure and function of human thought in practical scientific and continues to influence the ideas, opinions, mindset and actions of their day-to-day. The first innovation is Freud when he recognized a different mindset between the conscious mind and the subconscious mind. Under the influence of the subconscious thoughts and feelings are allocated out of place, where they can be put together and expressed through an abstract shape in which the objects can be a symbol of another incident.Analysis with Freud's theory as well as to analyze the work of artists who use the subject of personal experience to present ideas in the works he made, in the course of his work meyisakan various problems that are hidden from the memory of the past as well as to convey no meaning in every image ironic paradox sometimes unintentionally created in game visual artists at work in the fields or created in the space of expression for the artist or artist author. Keyword: Psychoanalysis Freud, the idea ofÂ Ã¢â‚¬â€¹Ã¢â‚¬â€¹the work from artists, Irony, Memory space Time